Keragaan Usaha Pengolahan Kopi Sedap Enak Rasanya (SER) pada UUP Mekar Sari, Banjar Jempanang, Desa Belok Sidan, Kecamatan Petang, Kabupaten Badung - SUCANTI, NI LUH PANDE; USTRIYANA, I NYOMAN GEDE; YUDHARI, DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.1, Januari 2015, 2016)
Diversity Of Coffee Processing Bussiness Coffee SER on UUP Mekar Sari, Br. Jempanang, Belok Sidan village, Petang Sub-district, Badung Regency. Abstract The effort of the Agricultural Development is to increase the productivity and plants diversification. The plantation has the strategic position in the agricultural development in Bali. O ne of the potensial agricultural comodity development s is coff e e. Based on the data is shown by the central statistic institution, Badung Regency is for of regencies in Bali that produces Arabi ca Coffe e in Bali is 683,14 ton . Coffee SER i t is the best coffe e product run by UUP Mekar Sari, Br. Jempanang, Belok Sidan village. This village is popular as the village company that run the public plantation and it is as Arabica irrigation or Subak Abian. The purpose of the research was descibing  the diversity of coffee processing bussiness that concisted of revenue and marketing of SER coffee. The research method used to apply the research was interviewed, observe in UUP Mekar Sari and studied literature. The result of research showed R/C ratio obtained 0,11. It meant, SER coffee production were able to get no beneficial. Marketing method consisted of marketed product by export quality. The priced to 100 gr packing was Rp 10.000 and the priced to 1 kg was Rp 100.000. The distribution of SER coffee it is support by Pacung Asri Restaurant which was the marketed directly to consumen by exhibition. To UUP Mekar Sari based on this research must improve the work quality which was made of the coffee by mix the ingridient of coffee and also sale and promote it used internet. Key word: Diversity Of Coffee Processing Bussiness, Coffee SER